Dramaturgi dalam Fenomena Curhat di Instagram Mahasiswa FISIP UNNES - Theodorus Zabdi Putra Dita; Fulia Aji Gustaman (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
This study reveals the motives for curhat on Instagram, as well as the front and backstage appearances. The approach used in this study is qualitative research with a descriptive research type. The dramaturgy theory proposed by Erving Goffman is used to describe the motives for curhat on Instagram. Based on the results of the study, there are three motives for curhat on Instagram. First, to overcome loneliness and the absence of friends to talk to. Second, self-presentation. Third, seeking validation and social support. In carrying out the activity of curhat on Instagram, it is evident that there is a dramaturgy practice carried out by students. The front stage aims to create the impression as expected. The front stage is divided into two parts, namely setting and personal front. Setting includes the selection of certain features, such as stories and feeds. Personal front includes appearances such as filters, song choices, and post designs. Styles such as captions use metaphors, poetic diction, and symbolism. While the backstage is related to considerations for uploading content and editing before appearing in public.